The Role of Servant Leadership and Self-Efficacy in Adaptive Performance - Haryanto, Teguh; Sutawijaya, Ahmad Hidayat (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Technological change is an opportunity to develop yourself and work better. The aim of this research is to determine the role of Servant Leadership and Self Efficacy on Adaptive Performance. It is hoped that this research can provide valuable insight for organizations in managing employee adaptation to technology and changes in their work in this ever-evolving era. The sampling method was purposive sampling by distributing questionnaires online to 105 respondents and using the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis method. The research results prove that Servant Leadership has a positive and significant effect on Adaptive Performance, Self Efficacy has a positive and significant effect on Adaptive Performance, Servant Leadership has a positive and significant effect on Self Efficacy and there is a positive and significant effect between Self Efficacy moderating the relationship between Servant Leadership and Adaptive Performance. Keywords: Servant Leadership, Self Efficacy and Adaptive Performance